Successful Management of a Posterior Post-Infarction Ventricular Septal Defect and Mitral Regurgitation with Delayed Surgery—A Case Report and Overview of the Literature - Mihai Ștefan; Mircea Robu; Cornelia Predoi; Răzvan Ilie Radu; Daniela Filipescu (Reports)
Background and Clinical Significance: Ventricular septal defect (VSD) is a rare but serious complication following myocardial infarction (MI) that can lead to cardiogenic shock and carries a high mortality rate. Acute mitral regurgitation (MR) is another severe complication of MI with additional risks of mortality. The optimal timing of surgical intervention for VSD with MR is still being debated, and delaying surgery in medically manageable patients has been associated with improved survival. However, managing these patients in the intensive care unit (ICU) presents unique challenges. Case Presentation: In this paper, we present the case of a 52-year-old male with comorbidities who developed post-MI VSD with severe MR and underwent successful delayed surgical repair and mitral valve replacement. Our aim is to highlight the clinical characteristics, diagnostic approach, and management strategies of this rare complication in the critical care setting. The patient presented in cardiogenic shock and acute pulmonary edema. After stabilization using an intra-aortic balloon pump, pre- and afterload reducing pharmacotherapy and non-invasive mechanical ventilation, a watchful waiting strategy was employed, and surgery was performed on day 21 after hospital admission. Surgery was performed under general anesthesia, and the patient did not develop any complications related to the intra-aortic balloon pump or novel organ dysfunction. Conclusions: This case highlights the importance of a multidisciplinary approach to managing post-MI VSD with MR and emphasizes the need for careful patient selection and timing of surgical intervention in the critical care setting. Clinicians should be aware of the potential benefits of delaying surgical intervention in medically manageable patients, while also considering the unique challenges of managing these patients in the ICU.